Hubungan Komunikasi Teraupetik Perawat dengan Kepuasan Klien Post Operasi di Rumah Sakit Umum Medan - Maria Haryanti Butarbutar; Yuly Peristiowati; Joko Prasetyo (Universitas Katolik Widya Karya Malang, 2023)
Hospital service quality can be seen from the professional appearance of hospital personnel, efficiency and effectiveness of services and patient satisfaction. Communication was very important for nurses in interacting with clines. Clines satisfaction is a level of patient feeling that arises as a result of health services performance obtained after patient compares it with expectation. clines satisfaction was determined by the overall service provided in patient or family complaints. The study was to determine the relationship between nurse communication and postoperative clines satisfaction at Medan Hospital.The research design used analytical survey method with a Cross-Sectional approach. The population in this study were postoperative patients totaling 477 respondents. The sampling used is purposive sampling, namely taking for a purpose by determining certain characteristics that are considered representative of the population, sampling is the slovin technique, totaling 83 respondents.The results of the analysis using the Chi-Square test showed that the significant probability value (Asymp.Sign) of nurse communication was 0.002 < sig value .05, this proves that there was a relationship between nurse communication and clines satisfaction at Medan Hospital.The conclusion was that statistically a relationship between nurse communication with postoperative clines at Medan Hospital. It is recommended for nurses to maintain communication therapeutic nurse to obtain quality health services for postoperative patients.